2005
DOI: 10.1121/1.1868212
|View full text |Cite
|
Sign up to set email alerts
|

Generation of longitudinal vibrations in piano strings: From physics to sound synthesis

Abstract: Longitudinal vibration of piano strings greatly contributes to the distinctive character of low piano notes. In this paper a simplified modal model is developed, which describes the generation of phantom partials and longitudinal free modes jointly. The model is based on the simplification that the coupling from the transverse vibration to the longitudinal polarization is unidirectional. The modal formulation makes it possible to predict the prominent components of longitudinal vibration as a function of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 20 publications
0
57
0
Order By: Relevance
“…Initially, P͑z͒ is a full string model, however, as theory and measurements indicate, the phantom partials do not appear at the same frequency range or frequencies as the transverse vibrations. 10,[19][20][21] Consequently, the unwanted low and high frequencies are filtered out with a bandpass filter D͑z͒.…”
Section: A General Description Of Synthesis Model and Timevarying Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, P͑z͒ is a full string model, however, as theory and measurements indicate, the phantom partials do not appear at the same frequency range or frequencies as the transverse vibrations. 10,[19][20][21] Consequently, the unwanted low and high frequencies are filtered out with a bandpass filter D͑z͒.…”
Section: A General Description Of Synthesis Model and Timevarying Stmentioning
confidence: 99%
“…20 Bank and Sujbert explain this to be a result of transverse to longitudinal coupling which is of a nonlinear nature. 21 Many synthesis models for this phenomenon have been proposed recently. [21][22][23] A computationally efficient solution, that follows the one discussed by Bank and Sujbert, 22 is proposed here.…”
Section: Introductionmentioning
confidence: 99%
“…Bank and Sujbert 4 have demonstrated that phantom partials are also generated by the longitudinal motion of the string as a response to the tension variation coming from the transverse string motion. Accordingly, "longitudinal components" refer to both longitudinal modes and phantom partials throughout the paper, and this study seeks the audibility limits of the longitudinal modes and phantom partials together.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, "longitudinal components" refer to both longitudinal modes and phantom partials throughout the paper, and this study seeks the audibility limits of the longitudinal modes and phantom partials together. For a detailed theoretical explanation the reader is referred to the above work 4 or to that of Watzky,5 who has investigated the longitudinal vibration of strings independently.…”
Section: Introductionmentioning
confidence: 99%
“…Some strictly adhere to an underlying physical model and require minimal assumptions, such as finite-difference time-domain methods (FDTD) [10,12]. Modal synthesis techniques, *Correspondence: l.gabrielli@univpm.it 1 Department of Information Engineering, Università Politecnica delle Marche, Via Brecce Bianche 12, Ancona 60131, Italy Full list of author information is available at the end of the article which enable accurate reproduction of inharmonicity and beating characteristics of each partial, have recently become popular in the modeling of stringed instruments [11,[13][14][15]. However, the computational model proposed in this paper is based on digital waveguide (DWG) techniques, which prove to be computationally more efficient than other methods while adequate for reproducing tones of slightly inharmonic stringed instruments [8,16,17] including keyboard instruments [18].…”
Section: Introductionmentioning
confidence: 99%